How to construct the most stable structure of (110) surface from rutile TiO2 bulk? - Tran Thi Thoa,; Nguyen Trong Nghia,; Hoang Van Hung,; Hue, Nguyen Thi Minh (Vietnam Journal of Science and Technology, 2024)
XRD pattern of rutile TiO2 bulk and surface energy of possible terminated (110) planes were investigated using the DFT+U method. The (110) surface was demonstrated to be the most popular facet of rutile TiO2, which is in good agreement with data of the JCPDS card No. 21-1276. The difference in surface energy among possible terminated (110) planes is attributed to structure of top and bottom atomic layers. We have found that the P5 plane is the most stable. It represents structure of (110) surface. Rutile TiO2 (110) surface has calculated surface energy of 0.98 J/m2. The value compares well with previous publications. Besides, DFT calculations were also performed. In comparison with DFT+U, surface energy obtained from DFT calculation for (110) surface is very small, about 0.48 J/m2.